Fouling mechanism elucidation in membrane bioreactors by bespoke physical cleaning - Di Bella, G.; Di Trapani, D.; Judd, Simon J. (Elsevier, 2018)
Cake layer deposition on a membrane surface can determine both external and internal membrane fouling through negatively affecting the total filtration resistance while exerting a positive effect as a pre-filter. Membranes are usually subjected to a periodic cake layer removal through routine physical cleaning, specifically permeate backwashing of hollow fiber membranes, or enhanced cleaning through, for example, chemically-enhanced backwashing. Physical cake layer removal is crucial for sustaining permeability, yet the effect of different physical cleaning modes remains poorly evaluated. The present work attempts to analyze physical cake layer removal through the application of specific cleaning methods and the impact of these on the subsequent resistance. The constituent contributions to the overall resistance are appraised by means of the Resistances In-Series model, with the aim of producing a robust protocol for quantifying these discrete contributors. The results, based in part on published data, show the proposed approach to reliably determine the relative contribution of the different resistance components to within 0.1 · 1012 m−1 across a range of different bench and pilot-scale plants, confirming the resilience of the method.
Keywords: Filter cake; Fouling; Backwashing; Physical cleaning; Resistance